Elliott Carter: Collected essays and lectures, 1937-1995 - Bernard, Jonathan W. (New York University of Rochester Press, 1997)
Elliott Carter (b.1908) is now generally acknowledged as America's most eminent living composer. This definitive volume of his essays and lectures - many previously unpublished or uncollected -shows his thinking and writing on music and associated issues developing in parallel with his career as a composer; his reputation became established in the 1950s, and the material in this book offers an important and knowledgeable commentary on the courseof American and European music in the succeeding decades. Carter's articles on his own music have become classic texts for students of his oeuvre; he also writes on the state of new music in Europe and the United States and the relations between music and the other arts. Other pieces range from a consideration of aspects of music to the work of individual composers. As a whole, the collection is the expression of Carter's musical philosophy, and a valuable record for historians of modern music.